2022
DOI: 10.1177/00219983221111491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the tensile properties of Sn-Zn-Ag lead-free solder alloy by loading MgO nanoparticles and irradiation

Abstract: Lead-free composite solders has attracted more attention as they are required in the microelectronics industry to assure good electrical connections and the best mechanical response between integrated circuit devices and the substrate. The mechanical mixing technique was used to prepare the plain (Sn-5.3 wt% Zn-1 wt% Ag, SZA531) and composite solder (SZA531/0.5 wt% MgO), while MgO nanoparticles were synthesized by sol-gel technique. The aim to investigate the effects of loading 0.5 wt% MgO NPs and [Formula: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The tensile characteristics of prepared films were investigated by recording the stress–strain curves utilizing a computerized, locally‐made tensile testing machine 23–25 . The films were separated into sections (pieces) that were sized like dumbbells that have 30 × 5 × ~0.20 mm dimensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile characteristics of prepared films were investigated by recording the stress–strain curves utilizing a computerized, locally‐made tensile testing machine 23–25 . The films were separated into sections (pieces) that were sized like dumbbells that have 30 × 5 × ~0.20 mm dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…The tensile characteristics of prepared films were investigated by recording the stress-strain curves utilizing a computerized, locally-made tensile testing machine. [23][24][25] The films were separated into sections (pieces) that were sized like dumbbells that have 30 Â 5 Â $0.20 mm dimensions. The films were stretched in only one dimension (uniaxially) until failure occurred at a constant crosshead speed of 0.5 mm/s.…”
Section: Measurementsmentioning
confidence: 99%
“…The strain rate sensitivity index decreased with higher doses and MgO loading due to reduced necking resistance, explained by Orowan and dislocation strengthening mechanisms. [ 18 ] Another study examined how adding SiC NPs affected the microstructure, thermal, and tensile properties of Sn–Zn–Ag solder alloy. Tensile tests showed that stress–strain curves varied with deformation temperature, strain rate, and SiC loading.…”
Section: Introductionmentioning
confidence: 99%